Developing a Design for Handling Problems for Community-Based Vulnerable Groups in Cipeuteuy Village, Kabandungan District, Sukabumi Regency - Yuliani, Dwi; Milenia, Aprilia Putri; Pohan, Hani Ulfah; Aribowo; Mildawati, Milly (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2024)
The study on Designs for handling the problem of Community-Based Vulnerable Groups is a study with the aim of developing previous designs which were only limited to handling children’s problems. The initial design for handling community-based children’s problems involved a community work team consisting of 10 community leaders from Cipeteuy Village Sukabumi Regency. The development of social problems and the need for handling them means that services provided are not only sufficient for choldren, but also for other vulnerable groups. This research is aimed at developing a design for handling problems of community-based vulnerable groups. In its implementation, this research used a qualitative approach with the Participatory Action Research method. This Method provides space for the community, facilitated by researchers, to develop ideas for handling the problems of vulnerable groups according to the strengths they have. The data collection techniques used were indepth interviewews, participant observation, documentation studies, and focus group discussions. The research results show community involvement in developing design for handling the problems of vulnerable groups by utilizing the strengths they have, as well as developing networks outside the community to make it easier to handle the problems of vulnareble groups consisting of neglected children, people with disabilities, neglected elderly, and other poor families who do not receive access to various service sources. The recommendation of this research is a design for community-based handling of vulnerable groups.